Does the chronic care model meet the emerging needs of people living with multimorbidity? A systematic review and thematic synthesis. - Kasey R Boehmer; Abd Moain Abu Dabrh; Michael R Gionfriddo; Patricia Erwin; Victor M Montori (PLoS ONE)
Background The Chronic Care Model (CCM) emerged in the 1990s as an approach to re-organize primary care and implement critical elements that enable it to proactively attend to patients with chronic conditions. The chronic care landscape has evolved further, as most patients now present with multiple chronic conditions and increasing psychosocial complexity. These patients face accumulating and overwhelming complexity resulting from the sum of uncoordinated responses to each of their problems. Minimally Disruptive Medicine (MDM) was proposed to respond to this challenge, aiming at improving outcomes that matter to patients with the smallest burden of treatment. We sought to critically appraise the extent to which MDM constructs (e.g., reducing patient work, improving patients' capacity) have been adopted within CCM implementations. Methods We conducted a systematic review and qualitative thematic synthesis of reports of CCM implementations published from 2011-2016. Results CCM implementations were mostly aligned with the healthcare system's goals, condition-specific, and targeted disease-specific outcomes or healthcare utilization. No CCM implementation addressed patient work. Few reduced treatment workload without adding additional tasks. Implementations supported patient capacity by offering information, but rarely offered practical resources (e.g., financial assistance, transportation), helped patients reframe their biography with chronic illness, or assisted them in engaging with a supportive social network. Few implementations aimed at improving functional status or quality of life, and only one-third of studies were targeted for patients of low socioeconomic status. Conclusion MDM provides a lens to operationalize how to care for patients with multiple chronic conditions, but its constructs remain mostly absent from how implementations of the CCM are currently reported. Improvements to the primary care of patients with multimorbidity may benefit from the application of MDM, and the current CCM implementations that do apply MDM constructs should be considered exemplars for future implementation work.